(untitled) (Faridpur Medical College Journal, 2021)
The first line antihypertensive treatment for severe hypertension of pregnancy includes labetalol, hydralazine, or nifedipine. Rapid but safe blood pressure control allows the definitive treatment, the delivery of baby to be carried out with minimal delay and good maternal and fetal outcomes. This non-randomized clinical trial was performed in Faridpur Medical College Hospital to compare the effectiveness and tolerability of oral nifedipine and intravenous labetalol in the acute control of severe hypertension of pregnancy. Total 50 admitted pregnant women with a viable fetus (>_ 24 weeks of gestation) having severe hypertension were allocated into two groups, Group A: 25 patients receiving oral nifedipine (10 mg), Group B: 25 patients receiving injectable labetalol (with incremental doses: 20, 40, 80mg). Up to 5 doses were tried for each drug at 15 minutes interval until target blood pressure (<_150/100 mmHg) was achieved. Baseline characteristics like mean age, mean weight, heart rate, systolic and diastolic pressures were similar in both labetalol and nifedipine groups. The average time required to achieve target blood pressure was 30.33 ± 10.44 minutes for labetalol and 25.63 ± 10.12 minutes for nifedipine (p=0.9129). Feto-maternal outcomes and adverse drug related effects were similar among the two groups. Both intravenous labetalol and oral nifedipine were found to be equally effective and well tolerated. Nifedipine may be preferable as it is a simple, flat dose schedule and an oral regimen. Faridpur Med. Coll. J. 2021;16(1):25-29